Conferencia. Obesity in developing countries: a possible role of early nutrition - Daniel J. Hoffman (Universidad de Antioquía, 2008)
During the past 30 years, it has beca me more accepted that growth retardation of a fetus or child is related to their state of health in adulthood, a concept commonly called the fetal origins hypothesis or the developmental origins of health and disease (DOHaD). The significance of DOHaD for developing countries is broad as countries with a high prevalence of undernutrition may be at risk for hosting a large population of adults at an increased risk for chronic diseases.